2021
DOI: 10.1101/2021.11.16.468438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A recurrent circuit links antagonistic cerebellar modules during associative motor learning

Abstract: The neural architecture of the cerebellum is thought to be specialized for performing supervised learning: specific error-related climbing fiber inputs are used to teach sensorimotor associations to small ensembles of Purkinje cells located in functionally distinct modules that operate independently of each other in a purely feedforward manner. Here, we test whether the basic operation of the cerebellum complies with this basic architecture in mice that learned a simple sensorimotor association during eyeblink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 119 publications
(173 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have suggested that the CR-related activities of PCs in animals transitioning from DEC to TEC paradigms share remarkable similarities and can be explained by a common inverse firing rate model 6 . However, more recent research challenges this notion, revealing that both facilitatory and suppressive modulations occur in PCs during DEC 50 . Consistently, we observed both task-related facilitation and suppression in the IpN neurons of both DEC- and TEC-trained mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the CR-related activities of PCs in animals transitioning from DEC to TEC paradigms share remarkable similarities and can be explained by a common inverse firing rate model 6 . However, more recent research challenges this notion, revealing that both facilitatory and suppressive modulations occur in PCs during DEC 50 . Consistently, we observed both task-related facilitation and suppression in the IpN neurons of both DEC- and TEC-trained mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our cANN contains three layers-an input layer (granule cells), a middle layer (Purkinje cells), and an output layer (nuclei neurons) -and consists of a conventionally reported feedforward pathway and a recently identified recurrent pathway that starts from the Purkinje cells (Fig. 1b) [48][49][50][51][52][53][54] . We designed the inputs/outputs of the cANN (Fig.…”
Section: The Cerebellar Ann Model As a Next-word Prediction Circuitmentioning
confidence: 99%
“…Our cANN is highly consistent with a wealth of anatomical and physiological knowledge. While conventional local circuit models of the cerebellum are feedforward circuits [60][61][62][63][64][65] , recent reports have demonstrated the existence and functional significance of a recurrent connection starting from the Purkinje cells [48][49][50][51][52][53][54][66][67][68] . Since both next-word prediction and syntactic processing are inaccurate in a cANN without the recurrent pathway (data not shown) and conventional feedforward models (Supplementary Fig.…”
Section: Anatomical and Physiological Support For The Cannmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas PCs in the downbound microzones show prominent velocity-related responses, those in the adjacent upbound microzones show an increase in activity that is antagonistic to the response of the downbound PCs and is more proportional to the position of the eyelid during the CR [28]. Whether the downbound and upbound PCs correspond perfectly or only grosso-modo to the zebrin-negative (Z-) and zebrin-positive (Z+) microzones, respectively, remains to be shown [26,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%